2007
DOI: 10.1103/physrevb.76.115101
|View full text |Cite
|
Sign up to set email alerts
|

Density functional study of the actinide nitrides

Abstract: The full potential all electron linearized augmented plane wave plus local orbitals (FP-LAPW + lo) method, as implemented in the suite of software WIEN2K, has been used to systematically investigate the structural, electronic, and magnetic properties of the actinide compounds AnN (An = Ac, Th, Pa, U, Np, Pu, Am). The theoretical formalism used is the generalized gradient approximation to density functional theory (GGA-DFT) with the Perdew-Burke-Ernzerhof (PBE) exchange-correlation functional.Each compound has … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
92
4
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(116 citation statements)
references
References 43 publications
19
92
4
1
Order By: Relevance
“…We find a favorable comparison with the AE [22] results for the various AcN compounds considered. For ThN, we obtain reasonable results without the inclusion of the Hubbard U parameter.…”
Section: Structural Propertiesmentioning
confidence: 85%
See 2 more Smart Citations
“…We find a favorable comparison with the AE [22] results for the various AcN compounds considered. For ThN, we obtain reasonable results without the inclusion of the Hubbard U parameter.…”
Section: Structural Propertiesmentioning
confidence: 85%
“…Atta-Fynn et al [22] treated all the nitrides on equal footing at different magnetic configurations with and without spin orbit coupling (SOC). They showed that the type-I antiferromagnetic (AFM) configuration gives similar results to the type-II AFM configuration and results in a more energetically favorable configuration with the inclusion of SOC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides playing an important role in both technological applications and environmental issues, Pu metal and its oxides show many intricate physical behaviors due to the complex electronic structure properties of 5f states [1][2][3][4]. Therefore, a thorough understanding of the physical and chemical properties of PuO 2 is of great significance, full of challenges and has always attracted attention.…”
Section: Introductionmentioning
confidence: 99%
“…[30], the same LAPW formalism within the GGA approximation was used to study the structural, electronic, and magnetic properties of the actinide compounds. The observed chemical bonding between the actinides and nitrogen was characterized by a significant ionic character.…”
Section: Previous Theoretical Simulations On Unmentioning
confidence: 99%